Analisis Framing Kompas.com Dalam Membentuk Opini Publik Terkait Makan Siang Bergizi Gratis - Ramadhani, Sifana Puspa; Alfirahmi, Alfirahmi (LUGAS Jurnal Komunikasi, 2025)
The Free Nutritious Lunch Program (MBG) has become a topic of public discussion since it is designated as a flagship government program for 2024–2029, prompting media outlets such as Kompas.com to report its progress continuously. This study aimed to identify and analyze how Kompas.com presented news regarding the MBG program and how such reporting shaped public opinion. A descriptive qualitative approach was employed, based on Robert Entman’s framing theory, which consisted of four components: defining problems, diagnosing causes, making moral judgments, and suggesting treatment recommendations. The findings indicated that Kompas.com highlighted the presence of the MBG program in meeting Indonesian children’s nutritional needs as the main issue, linked the causes of MBG-related problems more to technical and structural factors, built a positive narrative toward the government, and recommended enhanced monitoring of food distribution as well as training for the Nutrition Fulfillment Service Units (SPPG). Public opinion formed by the news was generally positive, although it occasionally fluctuated between neutral and positive depending on the news context.